The Impact of Green Banking Implementation on the Profitability and Performance of Indonesian Banks (The Period of 2021-2024) - Putri, Rafa Fahriela; Galuh, Ajeng Kartika (Contemporary Studies in Economic, Finance and Banking, 2026)
Green banking has emerged as a global strategic approach to support sustainability, yet its impact on bank profitability in Indonesia remains underexplored. This study aims to analyze the effect of green banking practices on the profitability of commercial banks listed on the Indonesia Stock Exchange. Using a quantitative approach, the study examines panel data from 13 banks over the 2021–2024 period through fixed effect regression analysis. Profitability is measured by Return on Assets (ROA). The independent variables include operational efficiency (operating expenses to operating income), capital adequacy ratio, sustainable financing (portion of green lending), digital service usage (number of e-banking users), number of ATMs, and Corporate Social Responsibility (CSR) funds. The results show that operational efficiency, sustainable financing, digitalization, and CSR funds significantly affect ROA. Meanwhile, capital adequacy and the number of ATMs have no significant effect. The study concludes that specific green banking practices can enhance profitability when implemented effectively. These findings contribute to the green banking literature in Indonesia and offer practical insights for banks and regulators in formulating sustainable finance policies.